The Shape of Blood Platelets - Murphy, Martin J., Jr. (Thrombosis and Haemostasis, 1972)
The three dimensional structure of human blood platelets has been investigated using two different methods of tissue preparation. It has been demonstrated that freeze-drying preserves platelet structure to a greater degree than other methods which employ air drying.When platelets are prepared by conventional techniques their dendritic projections are uniformly found to be flattened and in contact with the substrate when viewed by scanning electron microscopy. When lyophilisation is used some of these fine cytoplasmic protuberances are found to be freely directed away from the substrate and may in fact elevate the entire platelet body or chromomere. The possible implications of this new observation are discussed in terms of platelet ultrastructure and their role in hemostasis.